INSTRUMEN HOTS MATEMATIKA BAGI MAHASISWA PGSD - Syafri Ahmad; Ary Kiswanto Kenedi; Masniladevi Masniladevi (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The background of this research is that no standard instrument can measure the ability of HOTS PGSD students in lecturesin high-class mathematics education. This study aims to develop HOTS instruments that are valid, effective and practical.This research is development research. The results of this study were 1) produced valid devices based on expert judgment, 2)HOTS instruments produced were also effective in terms of increasing the HOTS category of PGSD students from the lowcategory up to the medium category, and 3) HOTS instruments categorized as very practical both from faculties of lecturersand students. This research implies that this instrument can be used as a standard measurement tool in knowing the ability ofHOTS PGSD students.